2021
DOI: 10.21037/tau-21-899
|View full text |Cite
|
Sign up to set email alerts
|

Kidney stone disease and cardiovascular events: a study on bidirectional causality based on mendelian randomization

Abstract: Background: Kidney stone disease (KSD) has been reported to be associated with several cardiovascular diseases. However, the causality between the conditions remains unknown. In the study, we performed a study on bidirectional causality by two-sample Mendelian randomization (MR) to investigate the causality between KSD and cardiovascular diseases including coronary atherosclerosis, hypertension, and cardiomyopathy.Methods: In the recent study, we performed a bidirectional two-sample MR study using available ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Reversely, Madore et al found that hypertension did not affect nephrolithiasis risk in men and wemon [ 37 , 38 ]. A previous MR analysis reported that kidney stone disease could unidirectionally increase the risk of hypertension with little impact (OR = 1.001) [ 11 ]. On the contrary, we verified that the presence of kidney stones was causally connected with high systolic and diastolic blood pressure (OR = 1.51, P = 0.0005; OR = 1.28, P = 0.0001, respectively), but not vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reversely, Madore et al found that hypertension did not affect nephrolithiasis risk in men and wemon [ 37 , 38 ]. A previous MR analysis reported that kidney stone disease could unidirectionally increase the risk of hypertension with little impact (OR = 1.001) [ 11 ]. On the contrary, we verified that the presence of kidney stones was causally connected with high systolic and diastolic blood pressure (OR = 1.51, P = 0.0005; OR = 1.28, P = 0.0001, respectively), but not vice versa.…”
Section: Discussionmentioning
confidence: 99%
“…By taking advantage of the random assortment of SNPs at conception, MR studies are less vulnerable to confounding and reverse causation bias than conventional observational studies [ 9 ]. Several MR analyses have explored the associations between single modifiable risk factors and kidney stones, such as obesity [ 10 ], T2D [ 10 ], cardiovascular events [ 11 ], coffee and caffeine consumption [ 12 ], education [ 13 ], serum urate [ 14 ], 25(OH)D [ 15 ], and calcium [ 16 ]. Here we aimed to extend our analysis to comprehensively estimate the causal effects of 47 potentially modifiable risk factors on the risk of kidney stones by using a bidirectional MR approach.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HBP, FL, and UpH presented a positive correlation with a higher risk for urolithiasis in both genders. Hypertension was reported to be associated with an increased risk of urolithiasis from epidemiological and genetic perspectives [ 28 ]. Federico et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, the correlation between A/G ratio and KSD was more significant in the hypertensive group. This may be because hypertension itself is a risk factor for KSD (53), so it enhances this correlation. Interestingly, diabetes itself is also a risk factor for KSD.…”
Section: Discussionmentioning
confidence: 99%